Improving mass transfer efficiency for penicillin production by using a continuous stirred tank reactor: a review - Al-Rekabi, Duaa; Rushdi, Salih (Pharmakeftiki, 2025)
Continuous stirred tank reactors (CSTRs) play a pivotal role in the industrial production of chemicals, including antibiotics such as penicillin, due to their ability to enhance mass transfer efficiency. The CSTR’s design facilitates precise control over aeration and agitation; two critical parameters that influence the volumetric mass transfer coefficient. Aeration supports cellular metabolism by supplying oxygen, while agitation promotes the dispersion of gas bubbles, thereby improving phase contact. This review explores the historical development of penicillin, its mechanism of action, the principles underlying bioreactor operation, and the specific ways in which aeration and agitation affect mass transfer dynamics. By optimizing reactor configuration, operating conditions, and associated process parameters, producers can significantly enhance the efficiency of penicillin biosynthesis.